2015
DOI: 10.1097/mib.0000000000000398
|View full text |Cite
|
Sign up to set email alerts
|

Properdin Regulation of Complement Activation Affects Colitis in Interleukin 10 Gene–Deficient Mice

Abstract: Complement is activated in the IL-10(-/-) mouse mucosa in a properdin-dependent manner. In the absence of terminal complement activation, the inflammation is heightened, likely due to a lack of neutrophil control over microbes escaping from the intestines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…In vivo mouse models have provided evidence for other potential consequences of systemic, long‐term properdin inhibition. P −/− mice exhibited worsened colitis, associated with decreased infiltration of neutrophils into the intestine and corresponding increases in bacterial burden in an IL‐10 −/− model of inflammatory bowel disease . Properdin deficiency was also shown to be detrimental in a mouse model of infectious colitis utilizing Citrobacter rodentium .…”
Section: Potential For Properdin Inhibitors As Long‐term Prophylacticmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo mouse models have provided evidence for other potential consequences of systemic, long‐term properdin inhibition. P −/− mice exhibited worsened colitis, associated with decreased infiltration of neutrophils into the intestine and corresponding increases in bacterial burden in an IL‐10 −/− model of inflammatory bowel disease . Properdin deficiency was also shown to be detrimental in a mouse model of infectious colitis utilizing Citrobacter rodentium .…”
Section: Potential For Properdin Inhibitors As Long‐term Prophylacticmentioning
confidence: 99%
“…P −/− mice exhibited worsened colitis, associated with decreased infiltration of neutrophils into the intestine and corresponding increases in bacterial burden in an IL-10 −/− model of inflammatory bowel disease. 184 Properdin deficiency was also shown to be detrimental in a mouse model of infectious colitis utilizing Citrobacter rodentium. Increased pathogenesis in this model was related to an increase in infiltrating neutrophils and macrophages as a result of a decreased ability of intestinal epithelial cells to control initial bacterial burden, which was shown to be dependent on properdin-mediated generation of C5a.…”
Section: Potential Consequences Of Properdin Inhibitionmentioning
confidence: 99%
“…On the contrary, in cases of infection where complement is directed to the invading pathogen, absence of properdin was often found detrimental for the host. Properdin deficiency has been associated with an exacerbated disease outcome in models of polymicrobial septic peritonitis [ 7 ], colitis [ 50 , 51 ], small intestinal mucositis [ 106 ], LPS-induced non-septic shock [ 107 ], and Listeria -induced septicemia [ 108 ]. In these cases, properdin-deficient mice likely had a detrimental outcome due to compromised host defense against the microbial intruder, indicating properdin played a crucial role in this process.…”
Section: Clinical Significance Of Properdinmentioning
confidence: 99%
“…In the small intestines, exposed to high fat diet, the complement transcriptome is increased [103] as epithelial cells react to support the mucosal barrier [104]. In a condition where epithelial integrity is compromised, we found that the absence of properdin led to enhanced bacterial translocation [105]. Therefore, we suggest that altered intestinal permeability in KO (which we did not measure) yields higher levels of endotoxin, fatty acids and lipids (which we measured).…”
Section: Discussionmentioning
confidence: 68%